Improving Dwell-Based Gaze Typing with Dynamic, Cascading Dwell Times - Mott, Martez E.; Williams, Shane; Wobbrock, Jacob O.; Morris, Meredith Ringel (Proceedings of CHI 2017, 2017)
We present cascading dwell gaze typing, a novel approach to dwell-based eye typing that dynamically adjusts the dwell time of keys in an on-screen keyboard based on the likelihood that a key will be selected next, and the location of the key on the keyboard. Our approach makes unlikely keys more difficult to select and likely keys easier to select by increasing and decreasing their required dwell times, respectively. To maintain a smooth typing rhythm for the user, we cascade the dwell time of likely keys, slowly decreasing the minimum allowable dwell time as a user enters text. Cascading the dwell time affords users the benefits of faster dwell times while causing little disruption to users’ typing cadence. Results from a longitudinal study with 17 non-disabled participants show that our dynamic cascading dwell technique was significantly faster than a static dwell approach. Participants were able to achieve typing speeds of 12.39 WPM on average with our cascading technique, whereas participants were able to achieve typing speeds of 10.62 WPM on average with a static dwell time approach. In a small evaluation conducted with five people with ALS, participants achieved average typing speeds of 9.51 WPM with our cascading dwell approach. These results show that our dynamic cascading dwell technique has the potential to improve gaze typing for users with and without disabilities.